2014
DOI: 10.1177/0143034314525511
|View full text |Cite
|
Sign up to set email alerts
|

The trajectories of child’s internalizing and externalizing problems, social competence and adolescent self-reported problems in a Finnish normal population sample

Abstract: Group-based modeling techniques are increasingly used in developmental studies to explore the patterns and co-occurrence of internalizing and externalizing problems. Social competence has been found to reciprocally influence internalizing and externalizing problems, but studies on its associations with different patterns of these problems are scarce. Using data from a Finnish longitudinal normal population sample, trajectories of internalizing and externalizing problems were formed using the Child Behavior

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 51 publications
2
21
0
Order By: Relevance
“…This is a well-documented finding in non-22q11.2DS research which has indicated that early symptoms of internalizing behaviors related to anxiety and depression in childhood have a negative impact on social outcomes in adolescence (Korhonen et al, 2014) and adulthood (Essau, Lewinsohn, Olaya, & Seeley, 2014; Maughan, Collishaw, & Stringaris, 2013). Internalizing symptoms have also been identified as related to functional outcomes (not specific to social functioning) in 22q11.2DS.…”
Section: Discussionmentioning
confidence: 62%
“…This is a well-documented finding in non-22q11.2DS research which has indicated that early symptoms of internalizing behaviors related to anxiety and depression in childhood have a negative impact on social outcomes in adolescence (Korhonen et al, 2014) and adulthood (Essau, Lewinsohn, Olaya, & Seeley, 2014; Maughan, Collishaw, & Stringaris, 2013). Internalizing symptoms have also been identified as related to functional outcomes (not specific to social functioning) in 22q11.2DS.…”
Section: Discussionmentioning
confidence: 62%
“…A handful of studies have identified developmental trajectories of internalizing problems from childhood to adolescence (Fanti and Henrich 2010;Korhonen et al, 2014;Letcher et al 2009;Nivard et al, 2017;Sterba et al 2007), showing between three and six trajectory groups. Using diverse measures including the Child Behavior Checklist (CBCL) and DAWBA, all of these studies identified both high and low trajectories, showing stable levels of either high or low internalizing problems, respectively, from childhood to adolescence.…”
Section: Trajectories Of Internalizing Problemsmentioning
confidence: 99%
“…Using diverse measures including the Child Behavior Checklist (CBCL) and DAWBA, all of these studies identified both high and low trajectories, showing stable levels of either high or low internalizing problems, respectively, from childhood to adolescence. Of these, the studies examining data from childhood through middle or late adolescence revealed both increasing and decreasing groups, where children show either an increase or decrease, respectively, from childhood to adolescence (Korhonen et al, 2014;Letcher et al 2009;Nivard et al, 2017). One of these studies also examined externalizing scores and modeled their co-occurrence across childhood and adolescence, showing an association particularly when problems started early (Nivard et al, 2017).…”
Section: Trajectories Of Internalizing Problemsmentioning
confidence: 99%
“…Distinct trajectories among children and adolescents are evident for a variety of mental health‐related constructs such as internalizing (social and emotional) problems (Dekker et al., ; Korhonen et al., ; Mazza, Fleming, Abbott, Haggerty, & Catalano, ; Weeks et al., ), externalizing (attention, hyperactivity, and conduct) problems (Korhonen et al., ; Pingault et al., ), and quality of life (Vella, Magee, & Cliff, ). Studies demonstrate that children fluctuate in their risk for mental health‐related problems, including moves above and below clinical and subclinical threshold values (Korhonen et al., ). Furthermore, it is likely that the distinct trajectories of various mental health‐related problems show similar trajectories for multiple discreet problems (Korhonen et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Half of psychiatric disorders have their onset before the age of 14 years (Kessler et al, 2005), and tend to persist throughout childhood and adolescence into adulthood (Costello, Mustillo, Erkanli, Keeler, & Angold, 2003). The early intervention of psychiatric disorders is critical to reducing the burden of problems during childhood (Tabone, Thompson, & Wiley, 2010;Thompson, 2009) and for healthy functioning later in life, including higher educational attainment and greater social competence (Dekker et al, 2007;Korhonen et al, 2014;Pingault et al, 2011). Hence, assessing children's overall levels of risk for mental health problems is an important endeavor.…”
Section: Introductionmentioning
confidence: 99%